Favorable Outcomes of a Direct Heart Transplantation Strategy in Selected Patients on Extracorporeal Membrane Oxygenation Support. Issue 4 (April 2020) - Coutance, Guillaume; Jacob, Nicolas; Demondion, Pierre; Nguyen, Lee S.; Bouglé, Adrien; Bréchot, Nicolas; Varnous, Shaida; Leprince, Pascal; Combes, Alain; Lebreton, Guillaume
Abstract : Objectives: Heart transplantation in patients supported by venoarterial extracorporeal membrane oxygenation has been associated with poor prognosis. A specific protocol for extracorporeal membrane oxygenation management encompassing patient selection, implantation strategy, and preoperative and perioperative treatment is applied at our institution. Our aim was to compare posttransplant outcomes of patients supported or not by extracorporeal membrane oxygenation at the time of heart transplantation. Design: A large observational single-center retrospective study was conducted. The primary endpoint was overall survival after heart transplantation. Secondary endpoints included death-censored rejection-free survival and the frequency of extracorporeal membrane oxygenation-related complications. Setting: One heart transplantation and extracorporeal membrane oxygenation high-volume center. Patients: All consecutive patients over 18 years old with a first noncombined heart transplantation performed between 2012 and 2016 were included. Interventions: None (retrospective observational study). Measurements and Main Results: Among the 415 transplanted patients, 118 (28.4%) were on extracorporeal membrane oxygenation at the time of transplantation (peripheral, 94%; intrathoracic, 6%). Median time on extracorporeal membrane oxygenation before heart transplantation was 9 days (interquartile range, 5–15 d) and median follow-up post heart transplantation was 20.7 months. Posttransplant survival did not differ significantly between the two groups (1-yr survival = 85.5% and 80.7% in extracorporeal membrane oxygenation vs nonextracorporeal membrane oxygenation patients; hazard ratio, 0.69; 95% CI, 0.43–1.11; p = 0.12, respectively). Donor age, body mass index, creatinine clearance, and ischemic time were independently associated with overall mortality, but not extracorporeal membrane oxygenation at the time of heart transplantation. Rejection-free survival also did not significantly differ between groups (hazard ratio, 0.85; 95% CI, 0.60–1.23; p = 0.39). Local wound infection was the most frequent complication after extracorporeal membrane oxygenation (37% of patients). Conclusions: With the implementation of a specific protocol, patients bridged to heart transplantation on extracorporeal membrane oxygenation had similar survival compared with those not supported by extracorporeal membrane oxygenation. Abstract : Supplemental Digital Content is available in the text.